A composite current collector and its preparation method and application

By using a composite material of carbon dots and a polymer having a conjugated structure in the first coating of the composite fluid collector, problems such as unstable conductivity, poor adhesion, and inability to solvent in the prior art are solved, and lower contact resistance and higher battery rate performance are achieved.

CN119029213BActive Publication Date: 2025-02-28JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411442026.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

On the basis of reducing the contact resistance between the active material and the current collector, the prior art still has problems such as unstable conductivity, poor adhesion, and inability to solvent.

Method used

By introducing a composite material of carbon dots and a polymer having a conjugated structure into the first coating of the composite fluid collection, the modified substrate can be coordinated to improve conductivity, conductivity stability, adhesion, corrosion resistance and solvent resistance.

Benefits of technology

The contact resistance between the composite liquid collector and the active material layer is reduced, the rate performance of the battery is improved, and the polarization and thermal effects of the battery are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a composite current collector and a preparation method and application thereof. The composite current collector comprises a substrate and a first coating located on at least one surface of the substrate; the first coating comprises a composite material, and the composite material comprises carbon dots and a polymer having a conjugated structure. The composite current collector provided by the present invention, through the introduction of the composite material in the first coating, under the synergistic effect of the carbon dots and the polymer having a conjugated structure, reduces the contact resistance between the composite current collector and the active material layer, and improves the conductivity, conductive stability, adhesion, corrosion resistance and solvent resistance of the composite current collector, reduces battery polarization and thermal effects, and improves the rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a composite current collector and a preparation method and application thereof. Background Art

[0002] The current collector refers to a structure or part that collects current, usually a metal foil material such as copper foil or aluminum foil. In the manufacturing process of non-aqueous secondary batteries, i.e. rechargeable batteries (such as lithium-ion batteries or sodium-ion batteries, etc.), since the rolled surface of general metal foils is relatively smooth, some problems will arise when coating active materials, such as poor wettability, loose bonding, low bonding strength, small bonding area, and difficulty in adhesion, which leads to large interface resistance between active materials and current collectors, easy to fall off, and great difficulty in coating.

[0003] In the process of making batteries, in order to reduce the contact resistance between the active material and the current collector, a conductive carbon layer is usually added between the current collector and the active material. For example, CN113140706A provides a battery carbon coating process and a method for preparing a lithium-ion battery, wherein a carbon coating slurry is made of 10%-20% by mass of conductive carbon black, 70%-80% of deionized water, 5%-10% of styrene-butadiene rubber and 2%-4% of a dispersant, and is sprayed onto the inner surface of a small-sized cylindrical steel shell or cylindrical aluminum shell of a lithium-ion battery to obtain a carbon-coated cylindrical steel shell or a carbon-coated cylindrical aluminum shell. Through the treatment of the carbon coating layer, the electronic conductivity of the current collector and the active material of the steel shell or aluminum shell is improved, thereby reducing the internal resistance of the lithium-ion battery. For another example, CN102832392A discloses a current collector carbon-coated aluminum foil and a preparation method thereof. The prepared current collector carbon-coated aluminum foil is a layer of composite conductive carbon with good dispersibility coated on the aluminum foil. The composite conductive carbon includes granular conductive carbon black and fibrous conductive carbon that have been pre-dispersed by a dispersant. The granular conductive carbon black and the fibrous conductive carbon filled between the granular conductive carbon black form a conductive network in the form of a mesh node, so that the current collector carbon-coated aluminum foil has a good conductive effect. In the above documents, a conductive carbon layer is added between the current collector and the active material. Although the contact resistance can be reduced to a certain extent, the conductive coating still has problems such as unstable conductivity, poor adhesion, and solvent resistance.

[0004] Therefore, how to further improve the conductive stability, adhesion and solvent resistance of the current collector while ensuring the reduction of the contact resistance between the active material and the current collector is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite current collector and a preparation method and application thereof. The composite current collector provided by the present invention, through the introduction of the composite material in the first coating layer, under the synergistic effect of the carbon dots and the polymer with a conjugated structure, reduces the contact resistance between the composite current collector and the active material layer, and improves the conductivity, conductive stability, adhesion, corrosion resistance and solvent resistance of the composite current collector, reduces the battery polarization and thermal effects, and improves the rate performance of the battery.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite current collector, comprising a substrate and a first coating located on at least one surface of the substrate; the first coating comprises a composite material, and the composite material comprises carbon dots and a polymer having a conjugated structure.

[0008] The composite current collector provided by the present invention improves the conductivity and conductive stability of the composite current collector by modifying the substrate through the composite material composed of the carbon dots in the first coating and the polymer with a conjugated structure, which can reduce the contact resistance between the composite current collector and the active material layer on the one hand; on the other hand, due to the compounding of the carbon dots, the corrosion resistance of the polymer with a conjugated structure is also improved, and the solvent resistance of the composite current collector is further improved, thereby reducing the battery polarization and thermal effects, and improving the battery rate performance.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] Preferably, the polymer having a conjugated structure is in-situ grown on the surface of the carbon dots.

[0011] Preferably, the average particle size of the carbon dots is 1-6 nm.

[0012] Preferably, the carbon dots also have functional groups on their surface, and the functional groups include hydrophilic groups;

[0013] Preferably, the polymer having a conjugated structure includes any one of polyaniline, polypyrrole, polythiophene or polyphenylene vinylene, or a combination of at least two thereof.

[0014] Preferably, the first coating layer further includes polydopamine, and the polydopamine is coupled to the polymer having a conjugated structure through the carbon dots.

[0015] Preferably, the first coating layer also includes a first binder.

[0016] Preferably, a second coating is further provided on the surface of the first coating away from the substrate, and the second coating comprises a conductive coating, and the conductive coating comprises a conductive material and a second binder.

[0017] Preferably, the thickness of the first coating is 0.5-2 μm.

[0018] Preferably, the thickness of the conductive coating is 1-5 μm.

[0019] In a second aspect, the present invention provides a method for preparing the composite current collector as described in the first aspect, the preparation method comprising the following steps:

[0020] A first mixed liquid is disposed on at least one surface of a substrate to obtain a first coating, wherein the first mixed liquid comprises a composite material, and the composite material comprises carbon dots and a polymer having a conjugated structure.

[0021] Preferably, the method for preparing the composite material comprises:

[0022] The carbon dots, monomers with a conjugated structure, an initiator and an acidic solution are mixed to carry out a first polymerization reaction to obtain a composite material of a polymer with a conjugated structure in situ grown on the surface of the carbon dots.

[0023] Preferably, the carbon dots also have functional groups on their surfaces, and the preparation method of the carbon dots having functional groups is as follows:

[0024] The carbon source and the nitrogen source are mixed and subjected to a hydrothermal reaction to obtain carbon dots with functional groups.

[0025] Preferably, the first mixed solution further comprises polydopamine, and the method for preparing the first mixed solution comprising polydopamine comprises:

[0026] Dopamine monomer, the composite material and alkaline metal initiator solution are mixed to obtain the first mixed solution, and the first mixed solution is disposed on at least one side of the substrate to obtain the first coating.

[0027] Preferably, the preparation method of disposing the first mixed liquid on at least one side surface of the substrate comprises:

[0028] The substrate is placed in the first mixed liquid, and the first mixed liquid is arranged on at least one side of the surface of the substrate by shaking on a shaking table.

[0029] Preferably, the second coating is prepared on the surface of the first coating away from the substrate, and the preparation method comprises:

[0030] A conductive material, a second binder and a solvent are mixed to obtain a conductive paste, and the mixed conductive paste is applied to the surface of the first coating to obtain the second coating.

[0031] In a third aspect, the present invention further provides a battery, wherein the battery comprises the composite current collector as described in the first aspect or the composite current collector prepared by the preparation method as described in the second aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The composite current collector provided by the present invention has the dispersibility and dispersion stability of the solvent, the carbon dot surface has abundant luminescent traps which are more conducive to electron exchange, and also has a large number of sp 2 Clusters can improve the charge transfer ability of conjugated polymers. The two work together to greatly improve the conductivity and conductive stability of the composite material, while also improving the corrosion resistance and solvent resistance of the composite material. Therefore, after the first coating containing the composite material is set on the surface of the substrate, on the one hand, it can reduce the contact resistance between the composite current collector and the active material layer; on the other hand, the corrosion resistance and solvent resistance of the composite current collector are also improved, thereby reducing the battery polarization and thermal effects, and improving the battery rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the structure of the composite current collector provided in Example 1.

[0035] Figure 2 This is a comparison chart of the electrical conductivity results of the modified carbon dot-polyaniline composite material in Example 1 and the polyaniline in Comparative Example 1.

[0036] Among them, 1-substrate, 2-first coating, 3-second coating. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0039] In the description of this application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.

[0040] In a specific embodiment, the present invention provides a composite current collector, which includes a substrate and a first coating located on at least one surface of the substrate; the first coating includes a composite material, and the composite material includes carbon dots and a polymer with a conjugated structure.

[0041] The composite current collector provided by the present invention has the dispersibility and dispersion stability of the solvent, the carbon dot surface has abundant luminescent traps which are more conducive to electron exchange, and also has a large number of sp 2 Clusters can improve the charge transfer ability of conjugated polymers. The two work together to greatly improve the conductivity and conductive stability of the composite material, while also improving the corrosion resistance and solvent resistance of the composite material. Therefore, after the first coating containing the composite material is set on the surface of the substrate, on the one hand, it can reduce the contact resistance between the composite current collector and the active material layer; on the other hand, the corrosion resistance and solvent resistance of the composite current collector are also improved, thereby reducing the battery polarization and thermal effects, and improving the battery rate performance.

[0042] In the present invention, the carbon dots in the first coating layer and the polymer having a conjugated structure are indispensable and work together to improve the conductivity, conductive stability, corrosion resistance and solvent resistance of the composite current collector.

[0043] As a preferred technical solution in a specific embodiment, the polymer monomer with a conjugated structure is grown in situ on the surface of the carbon dots.

[0044] In the present invention, polymer monomers with a conjugated structure can form a polymer composite material with a more regular structure and size and a more dispersed distribution by in-situ growth on the surface of carbon dots. The in-situ growth combination can simultaneously improve the dispersibility and conductivity of the conjugated polymer.

[0045] As a preferred technical solution in a specific implementation, the average particle size of the carbon dots is 1~6nm, for example 1nm, 2nm, 3nm, 4nm, 5nm or 6nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In the present invention, carbon dots play the role of "crystallization nucleating agent" in the process of in-situ growth of polymer monomers with conjugated structures into polymers. The average particle size of carbon dots is controlled to 1-6 nm, which can better control the structure and average particle size of the composite material, thereby improving the dispersibility and dispersion stability of the composite material.

[0047] As a preferred technical solution in a specific embodiment, the surface of the carbon dots also has functional groups, and the functional groups include hydrophilic groups.

[0048] In the present invention, the hydrophilic groups on the surface of the carbon dots can better improve the dispersibility and dispersion stability of the composite material in the solvent, thereby being more conducive to improving the conductive stability and solvent resistance of the composite current collector; further, the hydrophilic groups described in the present invention are selected by conventional technology, that is, the types of groups with hydrophilic properties that do not affect the performance of the carbon dots themselves, and the present invention is applicable to all of them, including but not limited to hydroxyl groups or carboxyl groups.

[0049] As a preferred technical solution in a specific embodiment, the polymer with a conjugated structure includes any one of polyaniline, polypyrrole, polythiophene or polyphenylene vinylene, or a combination of at least two thereof.

[0050] In the present invention, in addition to the above-defined polymer substance types with a conjugated structure, the present invention is also applicable to other substance types that are reasonably known to those skilled in the art and that also have a conjugated result and can achieve the same technical effect; further, the size of the polymer with a conjugated structure in the present invention is 40~200nm (for example, 40nm, 50nm, 75nm, 100nm, 125nm, 150nm, 175nm or 200nm, etc.), which is better for improving performance.

[0051] As a preferred technical solution in a specific embodiment, the first coating also includes polydopamine, and the polydopamine is coupled with the polymer having a conjugated structure through the carbon dots.

[0052] In the present invention, the addition of polydopamine in the first coating layer can, on the one hand, act as a binder, and no additional binder needs to be added to the first coating layer, and can also improve the bonding force between the composite current collector and the active material layer; on the other hand, it can improve the electrochemical stability of the composite current collector;

[0053] Furthermore, when there are hydrophilic groups in the carbon dots, they bond with the amino groups, hydroxyl groups, etc. in polydopamine, thereby realizing the mutual coupling of polydopamine and the polymer with a conjugated structure through the carbon dots, making the two firmly bonded and not easy to fall off, which is more conducive to improving the bonding force and electrochemical stability of the composite current collector;

[0054] As a preferred technical solution in a specific implementation, the first coating also includes a first binder.

[0055] In the present invention, if the first coating does not contain polydopamine, a conventional binder may be added to enhance the bonding strength between the first coating and the substrate; in addition, when the first coating contains polydopamine, a first binder may be additionally added to further enhance the bonding strength between the first coating and the substrate, and the present invention does not limit the specific material type of the first binder, and the present invention is applicable to any conventional binder type that can be used for coatings in the art and does not affect the performance of the composite material. For example, the first binder includes but is not limited to polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate or lithium alginate, any one or a combination of at least two thereof;

[0056] Specifically, the mass ratio of the binder to the composite material may be (1-10):(90-99).

[0057] As a preferred technical solution in a specific implementation, a second coating is further provided on the surface of the first coating away from the substrate, and the second coating includes a conductive coating, and the conductive coating includes a conductive material and a second adhesive.

[0058] Specifically, the thickness of the first coating is 0.5~2μm, for example, 0.5μm, 1μm, 1.5μm or 2μm; the thickness of the conductive coating is 1~5μm, for example, 1μm, 2μm, 3μm, 4μm or 5μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In the present invention, a conductive coating is further provided on the surface of the first coating, which can better achieve the adhesion between the foil, the first coating and the electrode active material layer and reduce the contact resistance; and the thickness of the first coating is adjusted to 0.5-2 μm and / or the thickness of the conductive coating is adjusted to 1-5 μm, which can ensure that the comprehensive properties of the composite current collector, such as conductivity, adhesion, and corrosion resistance, are better improved.

[0060] It should also be noted that the selection of the type and thickness of the substrate of the composite current collector in the present invention are conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs;

[0061] Optionally, the substrate includes but is not limited to metal foil, such as copper, aluminum or alloys thereof; a composite metal layer structure may also be provided, i.e., metal layers are formed on both surfaces of the base film in the thickness direction; the base film material is not specifically limited, and is a base film material for conventional composite current collectors; the metal layer may be formed by evaporation or the like, and its material may be selected from aluminum, copper, gold, silver, nickel or the like or alloys thereof;

[0062] Optionally, the thickness of the substrate may be 1 to 15 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, etc.

[0063] In another specific embodiment, the present invention provides a method for preparing the composite current collector as described in the above specific embodiment, the preparation method comprising the following steps:

[0064] A first mixed liquid is disposed on at least one surface of a substrate to obtain a first coating, wherein the first mixed liquid comprises a composite material, and the composite material comprises carbon dots and a polymer having a conjugated structure.

[0065] The preparation method provided by the invention has a simple preparation process and is suitable for large-scale production.

[0066] As another preferred technical solution in a specific embodiment, the preparation method of the composite material includes:

[0067] The carbon dots, monomers with a conjugated structure, an initiator and an acidic solution are mixed to carry out a first polymerization reaction to obtain a composite material of a polymer with a conjugated structure in situ grown on the surface of the carbon dots.

[0068] In the present invention, a polymer with a conjugated structure is obtained by in-situ polymerization on the surface of carbon dots, which increases the binding force between the two and can better exert their synergistic effect;

[0069] Optionally, the monomer having a conjugated structure includes but is not limited to any one or a combination of at least two of an aniline monomer, a pyrrole monomer, a thiophene monomer or a phenylacetylene monomer;

[0070] Optionally, the molar ratio of the monomer having a conjugated structure to the initiator is (1-5):1, such as 1:1, 2:1, 3:1, 4:1 or 5:1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0071] Optionally, the initiator comprises ammonium persulfate;

[0072] Optionally, the mass ratio of the carbon dots to the monomer having a conjugated structure is (0.8-1.5):1, such as 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0073] In the present invention, the more the amount of carbon dots added, the less the residue after the reaction between the carbon dots and the monomers with a conjugated structure, which is more conducive to improving the dispersibility and dispersion stability of the composite material. In combination with cost and performance factors, the mass ratio of the carbon dots to the monomers with a conjugated structure is regulated to (0.8-1.5):1, and the dispersibility and dispersion stability of the composite material are higher, and the cost is also lower;

[0074] Optionally, drying is performed after the first polymerization reaction, and the drying method includes freeze drying;

[0075] In the present invention, freeze drying can better maintain the morphology of the composite material;

[0076] Optionally, the first polymerization reaction can be carried out at room temperature (eg, 20-30° C.), and the specific polymerization time can be adaptively selected and adjusted according to the polymerization temperature and the state of the product, for example, 5-15 hours.

[0077] As another preferred technical solution in a specific embodiment, the carbon dots also have functional groups on their surfaces. The preparation method of the carbon dots having functional groups is as follows:

[0078] The carbon source and the nitrogen source are mixed and subjected to a hydrothermal reaction to obtain carbon dots with functional groups.

[0079] Optionally, the carbon source includes but is not limited to any one of protein, glucose, citric acid or chitosan or a combination of at least two thereof, and the nitrogen source includes but is not limited to metformin hydrochloride and / or diethylenetriaminepentaacetic acid;

[0080] Optionally, the molar ratio of carbon to nitrogen in the carbon source and the nitrogen source is 1:(0.3-0.4), such as 1:0.3 or 1:0.4, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0081] Optionally, the temperature of the hydrothermal reaction is 200-300°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, and the time of the hydrothermal reaction is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] As a preferred technical solution in another specific embodiment, the first mixed solution also includes polydopamine, and the preparation method of the first mixed solution including polydopamine includes:

[0083] Dopamine monomer, the composite material and alkaline metal initiator solution are mixed to obtain the first mixed solution, and the first mixed solution is disposed on at least one side of the substrate to obtain the first coating.

[0084] In the present invention, the first coating can be prepared in one step by in-situ polymerization coupling of dopamine and the composite material without adding an additional binder; and the strong interaction between the carbon dots, copper ions and dopamine is conducive to the rapid polymerization of dopamine at room temperature, thereby obtaining a carbon dot-polyaniline / polydopamine coating coupled with carbon dots, which is firmly bonded and not easy to fall off;

[0085] Optionally, the mass ratio of the composite material to the dopamine monomer is (6-13):1, such as 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1 or 13:1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0086] In the present invention, by adjusting the mass ratio of the composite material to the dopamine monomer to (6-13):1, it is more conducive to the structural stability of the two to be strongly influenced by each other.

[0087] Optionally, the pH value of the alkaline initiator solution is 8 to 9, for example 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9, etc., and the alkaline initiator solution includes Tris HCl buffer and metal salts, the metal element in the metal salt includes copper, and the types of metal salts include sulfates, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] Furthermore, the preparation method of disposing the first mixed liquid on at least one side surface of the substrate includes:

[0089] Placing the substrate in the first mixed solution, and using a shaking table to set the first mixed solution on at least one side of the substrate;

[0090] Optionally, the second polymerization reaction can be carried out at room temperature (eg, 20-30° C.), and the specific polymerization time can be adaptively selected and adjusted according to the polymerization temperature and the state of the product, for example, it can be 30-60 hours.

[0091] In the present invention, by means of shaking table oscillation, the material mixing can be ensured to be more uniform, and the coupling of polydopamine and the composite material can be more closely coupled, thereby improving the electrochemical stability and adhesion of the composite current collector; it should also be noted that in addition to the shaking table oscillation method, other methods, such as coating method, are also feasible in the present invention.

[0092] As another preferred technical solution in a specific embodiment, when the first coating does not contain polydopamine, the preparation method of the first coating is:

[0093] The composite material, the first binder and the solvent are mixed to obtain a first coating slurry, which is applied to the surface of at least one side of the substrate and dried to obtain a first coating structure.

[0094] That is, in the present invention, when the first coating layer contains the first binder, the first coating layer can be prepared by a conventional slurry coating method.

[0095] As a preferred technical solution in another specific embodiment, the second coating is prepared on the surface of the first coating away from the substrate, and the preparation method includes:

[0096] A conductive material, a second binder and a solvent are mixed to obtain a conductive paste, and the mixed conductive paste is applied to the surface of the first coating to obtain the second coating.

[0097] Optionally, the mass ratio of the conductive material, the second binder and the solvent is (30-45): (1-5): (50-69), such as 30:1:69, 40:3:57, 45:5:50, 30:5:65 or 40:5:55, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0098] It should be noted that the present invention does not specifically limit the selection of specific material types of the conductive material, the second binder and the solvent, and the present invention is applicable to any material type that can be used as the conductive coating;

[0099] For example, the conductive material includes but is not limited to any one of carbon black, carbon nanotubes, graphite, acetylene black or graphene, or a combination of at least two of them; the second binder includes but is not limited to any one of polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate or lithium alginate, or a combination of at least two of them; the solvent includes but is not limited to N-methylpyrrolidone (NMP).

[0100] In one embodiment, the present invention further provides a battery, wherein the battery comprises the composite current collector as described in one of the above embodiments or the composite current collector prepared by the preparation method as described in another of the above embodiments.

[0101] The composite current collector provided by the present invention can be used in both positive electrode sheets and negative electrode sheets, that is, an electrode active material layer is arranged on at least one side surface of the composite current collector (the electrode active material layer is located on the surface of the first coating layer or on the surface of the second coating layer), and the type of electrode sheet is selected according to the type of specific active material in the electrode active material layer; technical personnel in this field can make adaptive selection according to actual needs.

[0102] It should be noted that the present invention does not specifically limit the specific type of battery, and can be distinguished according to the type of material in the electrode plate, for example, it can be a lithium ion battery or a sodium ion battery; further, the battery can be a liquid battery, a solid battery or a semi-solid battery; the specific structure of the battery can be adaptively selected and adjusted according to actual needs;

[0103] In one embodiment, the battery includes a positive electrode plate, a negative electrode plate, an electrolyte (a non-aqueous liquid electrolyte, a gel electrolyte or a solid electrolyte, etc.) and a diaphragm (the diaphragm is optional, and if the electrolyte is a solid electrolyte, the diaphragm structure may not be included); and except for the application of the composite current collector, the other structures, material types, specific proportions and preparation processes in the battery are all conventional technical solutions.

[0104] Example 1

[0105] This embodiment 1 provides a composite current collector based on the above specific implementation manner and a method for preparing the composite current collector, which are as follows:

[0106] like Figure 1 As shown, the composite current collector includes a substrate 1 (aluminum foil) and a first coating 2 located on both sides of the substrate 1, and a second coating 3 (conductive coating) is also provided on the surface of the first coating 2 away from the substrate 1;

[0107] The thickness of the first coating 2 is 0.5 μm. The first coating 2 includes a composite material and polydopamine. The composite material includes carbon dots (average particle size is about 4 nm) and polyaniline. The surface of the carbon dots is modified with hydrophilic groups. Polyaniline grows in situ on the surface of the carbon dots. Polydopamine is coupled to the polymer with a conjugated structure through the carbon dots.

[0108] The thickness of the second coating layer 3 is 1 μm, and the second coating layer 3 includes a conductive carbon material (conductive carbon black) and polyvinylidene fluoride.

[0109] The preparation method of the composite current collector is as follows:

[0110] (1) Preparation of modified carbon dots-polyaniline composites:

[0111] Glucose (carbon source) and metformin hydrochloride (nitrogen source) were mixed at a molar ratio of carbon to nitrogen of 1:0.4, and subjected to hydrothermal reaction at 200°C for 2 hours. The reaction supernatant was centrifuged at 1100 r / min for 10 minutes in a high-speed centrifuge, and the collected supernatant was filtered with a 0.22 μm microporous filter membrane to obtain a carbon dot aqueous solution. The carbon dot aqueous solution was dialyzed in deionized water for 24 hours to obtain modified carbon dots with hydrophilic groups on the surface.

[0112] 40 mg of modified carbon dots were dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a stable modified carbon dots dispersion, and then 37.3 mg of aniline was added thereto; at the same time, 91.3 mg of ammonium persulfate was dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a uniform ammonium persulfate hydrochloric acid solution. Finally, the ammonium persulfate hydrochloric acid solution was slowly and evenly added to the dispersion of modified carbon dots and aniline, and the two reacted at 20°C for 10 hours (the first polymerization reaction). After the reaction, the modified carbon dots-polyaniline composite material was obtained after freeze drying (freeze drying conditions: time 24 hours, temperature -50±3°C, pressure 20Pa);

[0113] (2) Preparation of the first coating:

[0114] A 25 mmol / L Tris-HCl buffer was prepared, a 5 mmol / L copper sulfate solution was prepared in the buffer, and the pH of the buffer solution was adjusted to 8.5 with 0.1 mol / L hydrochloric acid to obtain a mixed solution 1; then the modified carbon dots-polyaniline composite material and dopamine in a mass ratio of 10:1 were dissolved in the mixed solution 1 to obtain a mixed solution 2; after rinsing the aluminum foil with deionized water for 25 minutes, the aluminum foil was placed in the prepared mixed solution 2, and the solution was placed in a constant temperature (25°C) shaker and slowly shaken for 42 hours, the aluminum foil was taken out and rinsed with deionized water for 12.5 minutes, ultrasonically cleaned for 12.5 minutes, and dried to obtain a first coating (modified carbon dots-polyaniline / polydopamine) on both sides of the aluminum foil (substrate);

[0115] (3) Preparation of the second coating:

[0116] Conductive carbon material (conductive carbon black), polyvinylidene fluoride and NMP are mixed in a mass ratio of 40:3:57 to prepare a conductive slurry, and the conductive slurry is evenly coated on the surface of the first coating layer and dried to obtain the composite current collector.

[0117] Example 2

[0118] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the mass of the modified carbon dots is 40 mg, the mass of aniline is 26.7 mg, and the mass of ammonium persulfate is 65.3 mg, that is, the mass ratio of the modified carbon dots to the aniline monomer is 1.5:1.

[0119] The rest of the preparation methods and parameters were the same as those in Example 1.

[0120] Example 3

[0121] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the mass of the modified carbon dots is 40 mg, the mass of aniline is 50 mg, and the mass of ammonium persulfate is 122.5 mg, that is, the mass ratio of the modified carbon dots to the aniline monomer is 0.8:1.

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 4 This example provides a composite current collector based on the above specific implementation and a method for preparing the composite current collector, as follows:

[0124] The composite current collector comprises a substrate (aluminum foil) and a first coating layer located on both sides of the substrate, and a second coating layer (conductive coating layer) is further disposed on the surface of the first coating layer away from the substrate;

[0125] The thickness of the first coating is 2 μm, the first coating comprises a composite material and polydopamine, the composite material comprises carbon dots (average particle size is 6 nm) and polyaniline, the surface of the carbon dots is modified with hydrophilic groups, polyaniline is in situ grown on the surface of the carbon dots, and polydopamine is coupled to the polymer having a conjugated structure through the carbon dots;

[0126] The thickness of the second coating layer is 5 μm, and the second coating layer includes a conductive carbon material (conductive carbon black) and polyvinylidene fluoride.

[0127] The preparation method of the composite current collector is as follows:

[0128] (1) Preparation of modified carbon dots-polyaniline composites:

[0129] Glucose (carbon source) and metformin hydrochloride (nitrogen source) were mixed at a molar ratio of carbon to nitrogen of 1:0.4, and hydrothermally reacted at 250°C for 4 hours. The reaction supernatant was centrifuged at 1100 r / min for 10 minutes in a high-speed centrifuge. The collected supernatant was filtered with a 0.22 μm microporous filter membrane to obtain a carbon dot aqueous solution. The carbon dot aqueous solution was dialyzed in deionized water for 24 hours to obtain modified carbon dots with hydrophilic groups on the surface. 40 mg of the modified carbon dots were dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a stable modified carbon dot dispersion, and 37.3 mg of aniline was added thereto. At the same time, 91.3 mg of ammonium persulfate was dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a uniform ammonium persulfate hydrochloric acid solution. Finally, the ammonium persulfate hydrochloric acid solution was slowly and evenly added to the dispersion of modified carbon dots and aniline, and the two were reacted at 20°C for 10 hours (the first polymerization reaction). After the reaction, the modified carbon dots-polyaniline composite material was obtained by freeze drying (freeze drying conditions: time 24 hours, temperature -50±3°C, pressure 20Pa).

[0130] (2) Preparation of the first coating:

[0131] A 25 mmol / L Tris-HCl buffer was prepared, a 5 mmol / L copper sulfate solution was prepared in the buffer, and the pH of the buffer solution was adjusted to 9 with 0.1 mol / L hydrochloric acid to obtain a mixed solution 1; then, the modified carbon dots-polyaniline composite material and dopamine with a mass ratio of 6:1 were dissolved in the mixed solution 1 to obtain a mixed solution 2; after rinsing the aluminum foil with deionized water for 25 minutes, the aluminum foil was placed in the prepared mixed solution 2, and the solution was placed in a constant temperature (25°C) shaker and slowly shaken for 42 hours, the aluminum foil was taken out and rinsed with deionized water for 12.5 minutes, ultrasonically cleaned for 12.5 minutes, and dried to obtain a first coating (modified carbon dots-polyaniline / polydopamine) on both sides of the aluminum foil (substrate);

[0132] (3) Preparation of the second coating:

[0133] Conductive carbon material (conductive carbon black), polyvinylidene fluoride and NMP are mixed in a mass ratio of 40:3:57 to prepare a conductive slurry, and the conductive slurry is evenly coated on the surface of the first coating layer and dried to obtain the composite current collector.

[0134] Example 5

[0135] This embodiment provides a composite current collector based on the above specific implementation manner and a method for preparing the composite current collector, which are as follows:

[0136] The composite current collector comprises a substrate (aluminum foil) and a first coating layer located on both sides of the substrate, and a second coating layer (conductive coating layer) is further disposed on the surface of the first coating layer away from the substrate;

[0137] The thickness of the first coating is 1 μm, the first coating comprises a composite material and polydopamine, the composite material comprises carbon dots (average particle size is 3 nm) and polyaniline, the surface of the carbon dots is modified with hydrophilic groups, polyaniline is in situ grown on the surface of the carbon dots, and polydopamine is coupled to the polymer having a conjugated structure through the carbon dots;

[0138] The thickness of the second coating layer is 2.5 μm, and the second coating layer includes a conductive carbon material (conductive carbon black) and polyvinylidene fluoride.

[0139] The preparation method of the composite current collector is as follows:

[0140] (1) Preparation of modified carbon dots-polyaniline composites:

[0141] Glucose (carbon source) and metformin hydrochloride (nitrogen source) were mixed at a molar ratio of carbon to nitrogen of 1:0.4, and hydrothermally reacted at 250°C for 1 hour. The reaction supernatant was centrifuged at 1100 r / min for 10 minutes in a high-speed centrifuge, and the collected supernatant was filtered with a 0.22 μm microporous filter membrane to obtain a carbon dot aqueous solution. The carbon dot aqueous solution was dialyzed in deionized water for 24 hours to obtain modified carbon dots with hydrophilic groups on the surface.

[0142] 40 mg of modified carbon dots were dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a stable modified carbon dots dispersion, and then 37.3 mg of aniline was added thereto; at the same time, 91.3 mg of ammonium persulfate was dissolved in 20 mL of 1.2 mol / L hydrochloric acid solution to form a uniform ammonium persulfate hydrochloric acid solution. Finally, the ammonium persulfate hydrochloric acid solution was slowly and evenly added to the dispersion of modified carbon dots and aniline, and the two reacted at 20 ° C for 10 hours (the first polymerization reaction). After the reaction, the modified carbon dots-polyaniline composite material was obtained after freeze drying (freeze drying conditions: time 24 hours, temperature -50 ± 3 ° C, pressure 20 Pa);

[0143] (2) Preparation of the first coating:

[0144] A 25 mmol / L Tris-HCl buffer was prepared, a 5 mmol / L copper sulfate solution was prepared in the buffer, and the pH of the buffer solution was adjusted to 9 with 0.1 mol / L hydrochloric acid to obtain a mixed solution 1; then, the modified carbon dots-polyaniline composite material and dopamine with a mass ratio of 13:1 were dissolved in the mixed solution 1 to obtain a mixed solution 2; after rinsing the aluminum foil with deionized water for 25 minutes, the aluminum foil was placed in the prepared mixed solution 2, and the solution was placed in a constant temperature (25°C) shaker and slowly shaken for 42 hours, the aluminum foil was taken out and rinsed with deionized water for 12.5 minutes, ultrasonically cleaned for 12.5 minutes, and dried to obtain a first coating (modified carbon dots-polyaniline / polydopamine) on both sides of the aluminum foil (substrate);

[0145] (3) Preparation of the second coating:

[0146] Conductive carbon material (conductive carbon black), polyvinylidene fluoride and NMP are mixed in a mass ratio of 40:3:57 to prepare a conductive slurry, and the conductive slurry is evenly coated on the surface of the first coating layer and dried to obtain the composite current collector.

[0147] Example 6

[0148] The difference between this embodiment and embodiment 1 is that in this embodiment, polyaniline is replaced by polypyrrole;

[0149] In the preparation method, the aniline monomer is replaced by a pyrrole monomer.

[0150] The rest of the preparation methods and parameters were the same as those in Example 1.

[0151] Example 7

[0152] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the mass ratio of modified carbon dots to aniline monomer is 2:1, and the mass adaptability of the initiator can be adjusted according to the ratio.

[0153] The rest of the preparation methods and parameters were the same as those in Example 1.

[0154] Example 8

[0155] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the mass ratio of modified carbon dots to aniline monomer is 0.5:1, and the mass adaptability of the initiator can be adjusted according to the ratio.

[0156] The rest of the preparation methods and parameters were the same as those in Example 1.

[0157] Example 9

[0158] The difference between this embodiment and embodiment 1 is that the first coating layer of this embodiment does not contain polydopamine;

[0159] In the preparation method, the preparation process of the first coating, i.e., step (2), is: directly mixing the modified carbon dot-polyaniline composite material and polyvinylidene fluoride in a mass ratio of 98.5:1.5, then adding NMP to obtain a first coating slurry, and coating the first coating slurry on both sides of the aluminum foil, and drying to obtain the first coating.

[0160] The rest of the preparation methods and parameters were the same as those in Example 1.

[0161] Example 10

[0162] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the modified carbon dot-polyaniline composite material to the dopamine monomer is 5:1.

[0163] The rest of the preparation methods and parameters were the same as those in Example 1.

[0164] Embodiment 11

[0165] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the modified carbon dot-polyaniline composite material to the dopamine monomer is 15:1.

[0166] The rest of the preparation methods and parameters were the same as those in Example 1.

[0167] Example 12

[0168] The difference between this embodiment and embodiment 1 is that the composite current collector of this embodiment does not contain a second coating layer.

[0169] In the preparation method, step (2) is not performed.

[0170] The rest of the preparation methods and parameters were the same as those in Example 1.

[0171] Comparative Example 1

[0172] The difference between this comparative example and Example 1 is that the first coating layer of this comparative example does not contain carbon dots, that is, the composite material is polyaniline.

[0173] In the preparation method, carbon dots are not prepared, and the polymerization of polyaniline is directly carried out.

[0174] The rest of the preparation methods and parameters were the same as those in Example 1.

[0175] Comparative Example 2

[0176] The difference between this comparative example and Example 1 is that the first coating layer of this comparative example does not contain polyaniline, that is, the composite material is carbon dots.

[0177] In the preparation method, after the carbon dots are prepared, step (2) is directly performed.

[0178] The rest of the preparation methods and parameters were the same as those in Example 1.

[0179] Comparative Example 3

[0180] The difference between this comparative example and Example 1 is that the first coating layer of this comparative example does not contain a composite material.

[0181] In the preparation method, the preparation of the composite material in step (1) is not performed, and the polymerization of polydopamine and the preparation of the first coating are directly performed.

[0182] The rest of the preparation methods and parameters were the same as those in Example 1.

[0183] Comparative Example 4

[0184] The difference between this comparative example and Example 1 is that in this comparative example, the positions of the first coating layer and the second coating layer are swapped, that is, the second coating layer is located on the surface of the first coating layer.

[0185] In the preparation method, step (3) of preparing the second coating on the surface of the aluminum foil is first performed, and then steps (1) and (2) are performed.

[0186] The rest of the preparation methods and parameters were the same as those in Example 1.

[0187] [Application and performance testing of composite current collectors]

[0188] Composite current collector test:

[0189] (I) Conductivity test: The composite current collectors provided in Examples 1-14 and Comparative Examples 1-4 were tested for conductivity using a four-probe method;

[0190] Figure 2 The conductivity results of the modified carbon dots-polyaniline composite material in Example 1 and the polyaniline in Comparative Example 1 are compared. Figure 2 It can be seen that the conductivity of polyaniline after carbon dot composite has been greatly improved;

[0191] (II) Solvent resistance test: The composite current collectors provided by Examples 1-12 and Comparative Examples 1-4 were immersed in an electrolyte of the same formula (the electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:60:10, and the concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L) for 24 hours. After the immersion, the number of wipe resistance was tested;

[0192] Positive electrode preparation and testing:

[0193] The composite current collectors provided in Examples 1-12 and Comparative Examples 1-4 were respectively used to prepare positive electrode sheets. The specific preparation process is as follows:

[0194] The positive electrode material lithium iron phosphate (LFP), conductive carbon black (SP), and binder polyvinylidene fluoride (PVDF) are mixed at a mass ratio of LFP:SP:PVDF=97.3:1:1.7, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry to obtain a positive electrode slurry for standby use, wherein the slurry has a solid content of 60%; the positive electrode slurry is coated on both sides of the composite current collector surface, and after the coating is completed, the electrode sheet is placed in an oven at 110°C for drying, and roller pressed to obtain a positive electrode sheet;

[0195] (III) Membrane resistance test: The positive electrode sheets provided in Examples 1-12 and Comparative Examples 1-4 were subjected to a membrane resistance test by a membrane resistance tester;

[0196] Battery preparation and testing:

[0197] Preparation of negative electrode sheet: Graphite (graphite is a single particle prepared from isotropic coke), conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, deionized water is added to mix to obtain negative electrode slurry, and then the negative electrode material is coated on one side of the copper foil, dried, and rolled to obtain a negative electrode sheet;

[0198] The positive electrode sheets provided in Examples 1-12 and Comparative Examples 1-4 are respectively stacked with the graphite negative electrode sheets and the isolation film (polypropylene isolation film) prepared above to form a stacked body, and soft-pack batteries are obtained through spot welding, packaging, liquid injection, baking, formation, aging, capacity division and other processes.

[0199] The injected electrolyte is an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20, and the concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte is 1.15 mol / L;

[0200] (IV) Battery internal resistance test: The batteries provided in Examples 1-12 and Comparative Examples 1-4 were subjected to an AC internal resistance test:

[0201] (V) Battery surface temperature test: The batteries provided in Examples 1-12 and Comparative Examples 1-4 were subjected to battery surface temperature monitoring by a temperature sensing line;

[0202] The test results of the above tests are shown in Table 1.

[0203] Table 1

[0204]

[0205] Depend on Figure 1 And Table 1 can be obtained:

[0206] From the data results of Examples 1-6, it can be seen that the composite current collector provided by the present invention, with the synergistic cooperation of carbon dots and polymers with conjugated structures, has a reduced contact resistance between the composite current collector and the active material layer, and the conductivity, conductive stability, adhesion, corrosion resistance and solvent resistance of the composite current collector are significantly improved.

[0207] From the data results of Example 1 and Examples 7 and 8, it can be seen that during the preparation of the composite material, the mass ratio of carbon dots to aniline monomers will affect the conductivity of the composite material. This is because if the ratio of the two is too small, it will affect the in-situ polymerization effect of aniline, thereby affecting the dispersibility and conductivity of the composite material.

[0208] It can be seen from the data results of Example 1 and Example 9 that if polydopamine is not added to the first coating, the corrosion resistance of the coating will be reduced to a certain extent. Polydopamine has strong corrosion resistance and can further enhance the corrosion resistance of the foil to the electrolyte.

[0209] From the data results of Example 1, Example 10 and Example 11, it can be seen that in the first coating, if the mass ratio of the composite material to the dopamine monomer is too large, it will not significantly affect the performance of the electrode and the battery cell, but it will increase the manufacturing cost. If it is too small, it will weaken the coupling effect between dopamine and the composite material, and reduce the adhesion and stability of the first coating and the current collector. From the data results of Example 1 and Example 12, it can be seen that adding a conductive coating on the basis of the first coating can further reduce the contact resistance and improve the conductivity.

[0210] From the data results of Example 1 and Comparative Examples 1-4, it can be seen that the composite current collector provided by the present invention, the carbon dots in the composite material and the polymer with a conjugated structure are indispensable and must be coordinated. The lack of any one of the substances cannot achieve the joint improvement of the comprehensive performance of the composite current collector, such as conductivity, corrosion resistance and solvent resistance.

[0211] In summary, the composite current collector provided by the present invention has the dispersibility and dispersion stability of the solvent, the carbon dot surface has abundant luminescent traps which are more conducive to electron exchange, and also has a large number of sp 2 Clusters can improve the charge transfer ability of conjugated polymers. The two work together to greatly improve the conductivity and conductive stability of the composite material, while also improving the corrosion resistance and solvent resistance of the composite material. Therefore, after the first coating containing the composite material is set on the surface of the substrate, on the one hand, it can reduce the contact resistance between the composite current collector and the active material layer; on the other hand, the corrosion resistance and solvent resistance of the composite current collector are also improved, thereby reducing the battery polarization and thermal effects, and improving the battery rate performance.

[0212] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite current collector, characterized in that: The composite current collector includes a substrate and a first coating located on at least one side of the substrate; the first coating includes a composite material, the composite material includes carbon dots and a polymer with a conjugated structure; the polymer with a conjugated structure is in situ grown on the surface of the carbon dots; the polymer with a conjugated structure includes any one of polyaniline, polypyrrole, polythiophene or polyphenylene vinylene, or a combination of at least two thereof.

2. The composite current collector according to claim 1, characterized in that: The composite material satisfies at least one of the following conditions (b) to (c): (b) the average particle size of the carbon dots is 1-6 nm; (c) The carbon dots also have functional groups on their surfaces, and the functional groups include hydrophilic groups.

3. The composite current collector according to claim 1 or 2, characterized in that: The first coating satisfies at least one of the following conditions (e) to (f): (e) the first coating layer further includes polydopamine, and the polydopamine is coupled to the polymer having a conjugated structure through the carbon dots; (f) The first coating layer further includes a first binder.

4. The composite current collector according to claim 1, characterized in that: A second coating is further disposed on a surface of the first coating away from the substrate. The second coating comprises a conductive coating, and the conductive coating comprises a conductive material and a second binder.

5. The composite current collector according to claim 4, characterized in that: The composite current collector satisfies at least one of the following conditions (g) to (h): (g) the thickness of the first coating is 0.5-2 μm; (h) The thickness of the conductive coating is 1-5 μm.

6. A method for preparing a composite current collector according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: A first mixed liquid is disposed on at least one surface of a substrate to obtain a first coating, wherein the first mixed liquid comprises a composite material, and the composite material comprises carbon dots and a polymer having a conjugated structure.

7. The preparation method according to claim 6, characterized in that: The preparation method of the composite material comprises: The carbon dots, monomers with a conjugated structure, an initiator and an acidic solution are mixed to carry out a first polymerization reaction to obtain a composite material of a polymer with a conjugated structure in situ grown on the surface of the carbon dots.

8. The preparation method according to claim 6 or 7, characterized in that: The carbon dots also have functional groups on their surfaces. The preparation method of the carbon dots having functional groups is as follows: The carbon source and the nitrogen source are mixed and subjected to a hydrothermal reaction to obtain carbon dots with functional groups.

9. The preparation method according to claim 6, characterized in that: The first mixed solution also includes polydopamine, and the preparation method of the first mixed solution including polydopamine includes: Dopamine monomer, the composite material and alkaline metal initiator solution are mixed to obtain the first mixed solution, and the first mixed solution is disposed on at least one side of the substrate to obtain the first coating.

10. The preparation method according to claim 9, characterized in that: The preparation method of placing the first mixed liquid on at least one side of the surface of the substrate comprises: The substrate is placed in the first mixed liquid, and the first mixed liquid is arranged on at least one side of the surface of the substrate by shaking on a shaking table.

11. The preparation method according to claim 6, characterized in that: A second coating is prepared on a surface of the first coating away from the substrate, the preparation method comprising: A conductive material, a second binder and a solvent are mixed to obtain a conductive paste, and the mixed conductive paste is applied to the surface of the first coating to obtain the second coating.

12. A battery, characterized in that: The battery comprises the composite current collector according to any one of claims 1 to 5 or the composite current collector prepared by the preparation method according to any one of claims 6 to 11.

Citation Information

Patent Citations

  • Current collector carbon coated aluminum foil and its preparation method

    CN102832392A

  • Battery carbon coating process and preparation method of lithium ion battery

    CN113140706A

  • Negative pole piece of sodium ion battery, electrochemical device and electronic equipment

    CN114709368A

  • Negative pole piece and manufacturing method thereof, battery cell, battery and electronic equipment

    CN115148955A